Peningkatan Kemampuan Berbicara Mahasiswa Melalui Model Pembelajaran Debat - Kurniati, Lisdwiana (JURNAL PESONA, 2017)
AbstractThis study aims to know studentsâ speaking ability through debate learning model. This study used classroom action research by using one class as a sample that consists of 30 students. The data were obtained based on the observation in each learning cycles. The result shows that debate can improve studentsâ ability with the significant increasing of average score in every cycle. The average score in the cycle I am 61.7 and in the cycle 2 is 70.8.Key Words: Speaking ability, debate, and motivation.Â